Investigation of functional variability and connectivity in temporal lobe epilepsy: A resting state fMRI study - Dumlu, Seda Nilgün; Ademoğlu, Ahmet; Sun, Wei (Neuroscience letters, 2020)
•Temporal lobe epilepsy patients show more functional variability compared to healthy controls.•The functional connectivity mostly decreases in temporal lobe epilepsy patients.•Functional connectivity results reveal a certain breakdown in frontoparietal, ventral attention and default mode networks in epileptic patients. It is crucial to reveal the variability between patients with epilepsy and healthy subjects to elucidate the underpinnings of the disease pathology. Herein, we assessed the inter-subject variability between patients with temporal lobe epilepsy (TLE) and healthy subjects in terms of estimating the functional connectivity using resting-state functional magnetic resonance (rs-fMRI) scans. According to inter-subject variability results between healthy and TLE population, the latter showed more variability mainly in frontoparietal control, default mode, dorsal/ventral attention, visual and somatomotor networks in line with the broad seizure onset and propagation pathway. As a result of 17-Network parcellation, a significant attenuation is observed in functional connectivity, mostly in bilateral frontoparietal control, somatomotor, default mode and ventral attention networks associated with the functional impairment in attention, long/short term memory, executive functioning. The results are in favor of the argument that the functional disruption in TLE spreads throughout the cortex beyond the temporal lobe with an implication of greater diversity in the TLE population.